Forecasting Internalizing Psychopathology in Adolescents: A Gradient Boosting Approach to Parental Expressed Emotion, Adverse Childhood Experiences (ACEs), and Cognitive Reappraisal - Niyonsenga, Jean-Claude; Hoffmann, Lena; Menjívar, Carlos (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The objective of this study was to prospectively forecast adolescent internalizing psychopathology over an 18-month period by modeling the complex, non-linear interactions between cumulative adverse childhood experiences (ACEs), parental expressed emotion, and habitual cognitive reappraisal using a machine learning framework. Methods and Materials: This prospective longitudinal study utilized a sample of German adolescent-parent dyads. Baseline (T1) predictors included cumulative trauma assessed via the Adverse Childhood Experiences Questionnaire (ACE-Q), habitual emotion regulation measured by the Emotion Regulation Questionnaire (ERQ), and Parental Expressed Emotion (criticism and emotional over-involvement) derived from the Five-Minute Speech Sample (FMSS). The primary outcome, adolescent internalizing psychopathology at an 18-month follow-up (T2), was assessed using the Youth Self-Report (YSR). Data were analyzed using a gradient boosting regression ensemble, evaluated via an train-test split and 10-fold cross-validation, to capture higher-order non-linear predictive topologies without requiring a priori specification. Findings: The gradient boosting regression model demonstrated robust forecasting accuracy on the unseen test set, successfully predicting a significant portion of the variance in T2 internalizing symptoms ( , ), yielding a coefficient of determination of , with a Mean Absolute Error ( ) of and a Root Mean Square Error ( ) of . Bivariate analyses confirmed foundational relationships, showing positive correlations between ACEs and T2 internalizing symptoms ( ) and protective, negative correlations for cognitive reappraisal ( ). Multivariate feature importance extraction revealed a distinct predictive hierarchy: cumulative ACEs emerged as the single most dominant forecasting variable ( relative importance), followed significantly by parental criticism ( ), cognitive reappraisal ( ), and parental emotional over-involvement ( ). Conclusion: Cumulative childhood trauma and proximal parental criticism serve as the primary structural catalysts for future adolescent internalizing distress, whereas the adolescent’s habitual capacity for cognitive reappraisal offers a vital, quantifiable counterweight for psychological resilience.